Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/ef401658p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcination and Acidification on Structural Characterization of Anyang Anthracites

Abstract: The structural parameters of six coals were determined by X-ray diffraction (XRD), scanning electron microscope (SEM), and Raman and FTIR spectroscopy. The results reveal that the derivative coals prepared by calcination and HF acidification contain much crystalline carbon like graphite structure and are improved significantly in aromaticity, coal rank, and hydroxyl concentration. The increase of hydroxyl (OH) bonds is very beneficial to the surface modification of coal crystalline layers. In addition, the der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…The FTIR spectra of raw and MA are shown in Figure . We observe stretching vibrations and in‐plane vibrations of the hydroxyl bonds (OH) at the spectral peaks at 3100–3600 and 1400 cm −1 , respectively . After modification of the coal, the strength of these peaks is decreased, which corresponds to a decrease in the hydroxyl content on the coal surface; silanol formed by the hydrolysis of the silane coupling agent can react with and consume hydroxyl groups or cover their signals.…”
Section: Resultsmentioning
confidence: 96%
“…The FTIR spectra of raw and MA are shown in Figure . We observe stretching vibrations and in‐plane vibrations of the hydroxyl bonds (OH) at the spectral peaks at 3100–3600 and 1400 cm −1 , respectively . After modification of the coal, the strength of these peaks is decreased, which corresponds to a decrease in the hydroxyl content on the coal surface; silanol formed by the hydrolysis of the silane coupling agent can react with and consume hydroxyl groups or cover their signals.…”
Section: Resultsmentioning
confidence: 96%
“…A lot of amorphous carbons are in the internal of ICA due to the underdevelopment of carbon crystallites structure. It has been confirmed that the ( γ ) band around 20° is the amorphous carbon such as aliphatic side chains …”
Section: Resultsmentioning
confidence: 90%
“…Then, the radical polymerization reactions among the tar intermediates played a leading role, which would produce heavy tar or char fragments. Obviously, the free‐radical recombination reaction would reduce the tar yield …”
Section: Resultsmentioning
confidence: 99%